Papua People and Its Culture - Petrus Tekege; Roy Marthen Rahanra (Lakhomi Journal Scientific Journal of Culture, 2022)
The writing of this article is to understand Papuan people and their culture starting from the form of race, hair, skin, population distribution, customs manifested in the marriage system. This research method is socio-ethnographic, namely to provide an illustration that Papuans have one identity and a structured culture that is different, although not all of them with other ethnic groups in Indonesia. Based on the results of the study, it was found that race, hair, skin and the type or pattern of leadership as well as the existing marriage system were increasingly changing following the flow of globalization. Not all aspects of Papuan identity should change, some have to be authenticated and therefore traditional leaders need to play a maximum role in caring for, maintaining so that the values and aesthetics of cultural life can be seen and preserved.